Microstructure and Wear Behavior of Hardfacing with Ferro-alloy Powder Addition Using Submerged Arc Welding - Buntoeng Srikarun (Science Faculty of Chiang Mai University, 2019)
Hardfacing deposits with the additional metal powder become an intense development in the wear resistant applications. Low carbon steel electrode with carbon and chromium powder addition is used to improve the wear resistance of engineering components due to its martensite microstructure. The objectives of this research are to investigate the effect of ferro carbon, ferro chromium, and the mixture of ferro carbon and ferro chromium powder addition to the low carbon steel electrode deposits and compared to the standard martensitic steel type electrode without powder addition. Low alloy cast steel was hardfaced by submerged arc welding (SAW) process. The chemical composition of the weld metal for all conditions was studied using Optical Emission Spectrometer (OES) and Energy Dispersive X-ray Spectroscopy (EDS). Optical Microscope (OM), Scanning Electron Microscope (SEM) and X-Ray Diffraction (XRD) were used to analyze the metallurgical properties of the samples. Vickers hardness test and a dry sand rubber wheel abrasion test were also conducted. The results showed that the martensite microstructure varied with the welding conditions. The best abrasive wear resistance was obtained in the microstructure composed of a large martensite with dendritic ferrite, while the higher abrasive mass loss was measured in the microstructure of martensite with retained austenite. The main wear mechanisms observed at the worn surfaces included micro-cutting and micro-ploughing of the soft matrix and brittle fracture of the martensite structure.